Analisis Perubahan Kebijakan Luar Negeri Tun Mahathir terhadap Investasi Megaproyek Tiongkok di Malaysia - Erdiatulha; Lalu Puttrawandi Karjaya; Khairur Rizki (Indonesian Journal of Global Discourse, 2020)
This article examines the process of changing Tun Mahathir Mohamad's Foreign Policy towards Chinese megaprojects investment in Malaysia. After his re-inauguration as Prime Minister of Malaysia, Tun Mahathir decided to reject 14 MoUworth RM 143.64 Billion containing investment in Chinese projects in Malaysia and is a legacy of comprehensive cooperation between Najib Razak and China in 2016. The rejection was conveyed by Mahathir during his visit to China in August 2018. And, after that in April 2019, Mahathir changed his decision by resuming the megaproject that had been rejected. In analyzing tun Mahathir's policy change process, this paper combines two models of foreign politicy theory from Snyder which is Decision Making and Adaptive from Rosenau. The results showed that leadership were an important factor in the process of changing Mahathir policy and Supplementary Agreement becomes Mahathir’s reference of foreign policy changes to Chinese megaprojects investment in Malaysia.